Physical Activity Behavior and Mental Health Among University Students During COVID-19 Lockdown - Coakley, Kathryn E.; Lardier, David T.; Holladay, Kelley R.; Amorim, Fabiano T.; Zuhl, Micah N. (Frontiers in Sports and Active Living, 2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic placed social, travel, school access, and learning restrictions on University students. Excessive restriction measures have been shown to have negative impacts on mental health. Physical activity preserves mental health, and may be useful during quarantines. Purpose: Explore physical activity and sedentary behavior and associations with depression and anxiety symptoms among University students during COVID-19 restrictions in the Fall 2020 semester. Methods: Six hundred and ninety-seven undergraduates (18–25 years) from a U.S. public University completed a cross-sectional survey in fall 2020. The survey included demographic questions, the Generalized Anxiety Disorder Scale 7 (GAD-7), the Patient Health Questionnaire 9 (PHQ-9), and questions about meeting moderate to vigorous physical activity (MVPA) recommendations and sedentary behavior. Results: Forty-nine percent did not meet MVPA guidelines. Patient Health Questionnaire 9 (p = 0.002) and GAD-7 (p = 0.024) scores were higher among those who did not achieve MVPA. Sitting time (h/day) was a significant associated with depression (B = 0.29 (0.06), p < 0.05, 95% CI = 0.18, 0.41) and anxiety (B = 0.24 (0.05), p < 0.05, 95% CI = 0.13, 0.34) severity. Conclusion: Physical activity was associated with mental health among University students during COVID-19 lockdowns.